Analysis of risk factors and treatment strategies for lumbar cistern blockage after craniocerebral surgery - Zheng, Min; Tian, Qilong; Wang, Xuejiao; Liu, Liqin; Deng, Xiurui; Qu, Yan; Cai, Qing (Frontiers in Neuroscience, 2023)
Objective Lumbar cistern blockage is a common complication of continuous lumbar cistern drainage. This paper analyzes the risk factors for lumbar cistern blockage drainage due to various causes and proposes a series of prevention and intervention measures to reduce blockage or improve recanalization after blockage. Methods The clinical data of 637 patients with various lesions who underwent lumbar cistern drainage in our hospital were retrospectively collected and analyzed. Perioperative clinical and imaging data were assessed. Variates were analyzed using univariate and multivariate logistic regression analyses. Results A total of 13.7% (87/637) of patients had lumbar cistern blockage. Multivariate analysis revealed that drainage time (≥7 days), CSF volume <200 (mL/d), CSF leakage, and abnormal CSF properties were predictors of lumbar cistern blockage. Reducing the probability of lumbar cistern blockage can be achieved by repeatedly flushing, increasing the drainage flow and shortening the drainage time. The recanalization rate after blockage was 67.8% (59/87). After the drainage tube was removed, no complications related to the drainage tube occurred during the 1-week follow-up. Conclusion Lumbar cistern blockage is the main reason for poor drainage. Prevention or early intervention can effectively reduce the probability of blockage and achieve the purpose of drainage of cerebrospinal fluid.